Discovering the electronic circuit diagram of life: structural relationships among transition metal binding sites in oxidoreductases - Kim, J. Dongun (The Royal Society, 2013)
Oxidoreductases play a central role in catalysing enzymatic electron-transfer reactions across the tree of life. To first order, the equilibrium thermodynamic properties of these proteins are governed by protein folds associated with specific transition metals and ligands at the active site. A global analysis of holoenzyme structures and functions suggests that there are fewer than approximately 500 fundamental oxidoreductases, which can be further clustered into 35 unique groups. These catalysts evolved in prokaryotes early in the Earth's history and are largely responsible for the emergence of non-equilibrium biogeochemical cycles on the planet's surface. Although the evolutionary history of the amino acid sequences in the oxidoreductases is very difficult to reconstruct due to gene duplication and horizontal gene transfer, the evolution of the folds in the catalytic sites can potentially be used to infer the history of these enzymes. Using a novel, yet simple analysis of the secondary structures associated with the ligands in oxidoreductases, we developed a structural phylogeny of these enzymes. The results of this ‘composome’ analysis suggest an early split from a basal set of a small group of proteins dominated by loop structures into two families of oxidoreductases, one dominated by α-helices and the second by β-sheets. The structural evolutionary patterns in both clades trace redox gradients and increased hydrogen bond energy in the active sites. The overall pattern suggests that the evolution of the oxidoreductases led to decreased entropy in the transition metal folds over approximately 2.5 billion years, allowing the enzymes to use increasingly oxidized substrates with high specificity.